The role of magnetite-rich environments in prebiotic chemistry and astrobiology: insights into serpentinization processes on Mars - Nair, Varsha M.; Jagmag, Sana Hasan; Basu Sarbadhikari, Amit (Frontiers in Astronomy and Space Sciences, 2025)
Magnetite (Fe3O4), a common byproduct associated with the serpentine deposits, plays a pivotal role in catalyzing prebiotic chemical pathways to produce several important biological precursors relevant to the origin of life. On Mars, serpentine is identified on the Noachian surface, denoting the period of abundant surface water and water-rock interactions. During serpentinization, magnetite commonly forms as a byproduct controlled mainly by Fe-Mg lattice diffusion in olivine, contributing to reducing gases like hydrogen and methane through iron oxidation. This study utilizes selected analog serpentinized sites to investigate the critical role of magnetite in catalyzing and, therefore, facilitating key prebiotic pathways. The various sites are rift settings, obducted settings, plate-margin, and intraplate settings. This helps to understand the probable mineral assemblages associated with magnetite and potential prebiotic pathways in various settings and chemical environments. We discuss here the potential prebiotic pathways like Fischer-Tropsch Synthesis, Water Gas Shift, Haber-Bosch process, role of cyanide in magnetite preservation, and abiotic organic synthesis in the context of magnetite’s role as a potential catalytic surface and mineralogical marker in serpentinization systems. We also explore the potential role of subzero interfacial water films in mediating oxidant decomposition and magnetite-driven redox reactions, highlighting their implications for low-temperature serpentinization and habitability on Mars. This study may advance our understanding in shortlisting the prime targets for prebiotic studies, astrobiological investigations, and Mars sample return missions.